Subcloning Plus Insertion (SPI) - A Novel Recombineering Method for the Rapid Construction of Gene Targeting Vectors - Reddy, Thimma R. (J Vis Exp, 2015)
Gene targeting refers to the precise modification of a genetic locus using homologous recombination. The generation of novel cell lines and transgenic mouse models using this method necessitates the construction of a ‘targeting’ vector, which contains homologous DNA sequences to the target gene, and has for many years been a limiting step in the process. Vector construction can be performed in vivo in Escherichia coli cells using homologous recombination mediated by phage recombinases using a technique termed recombineering. Recombineering is the preferred technique to subclone the long homology sequences (>4kb) and various targeting elements including selection markers that are required to mediate efficient allelic exchange between a targeting vector and its cognate genomic locus. Typical recombineering protocols follow an iterative scheme of step-wise integration of the targeting elements and require intermediate purification and transformation steps. Here, we present a novel recombineering methodology of vector assembly using a multiplex approach. Plasmid gap repair is performed by the simultaneous capture of genomic sequence from mouse Bacterial Artificial Chromosome libraries and the insertion of dual bacterial and mammalian selection markers. This subcloning plus insertion method is highly efficient and yields a majority of correct recombinants. We present data for the construction of different types of conditional gene knockout, or knock-in, vectors and BAC reporter vectors that have been constructed using this method. SPI vector construction greatly extends the repertoire of the recombineering toolbox and provides a simple, rapid and cost-effective method of constructing these highly complex vectors.